Seni Seudati: Media Edukasi Sufistik dalam Mengembangkan Nilai Socio-Religius Masyarakat Aceh - Ridwan Hasan (IAIN Ponorogo, 2013)
Abstract: This article is aimed at describing the relevance of Seudati dance as a medium of mysticism (Sufism) education to develop and build socio-religious values of Aceh community and their awareness. This is due to the reason that Seudati dance is one of the educational media that can be used as a transformational medium of socio-religious values of community. Aceh Documentation Board has noted that Seudati dance has become mysticism (Sufism) educational medium actively in communicating the religious values to public. This qualitative study shows that Seudati dance has become an alternative educational medium to educate the whole positive values of Acehnese community, although their legality is still being debated by minority up to now. That is why, apart from pros or cons, Seudati dance as the medium of mysticism needs to be considered to increase the public awareness of Aceh community. Based on the number of theories and studies on the art of Seudati dance, this dance as the medium of mysticism education is very effective to build the values of socio-religious of Acehnese community. Therefore, the approach of mysticism education uses this dance as the medium of education to communicate the relevant and adaptive values inside it to public.